KONSTRUKSI HAKIKAT HUKUM ISLAM DALAM PERSPEKTIF FILSAFAT HUKUM: INTEGRASI DIMENSI TRANSENDENTAL, MORAL, DAN SOSIAL - Ihsan, Muhammad Hairul (Mitsaqan Ghalizan, 2025)
This article aims to reconstruct the understanding of the nature of Islamic law within the framework of legal philosophy, by emphasizing the importance of integration between transcendental, moral, and social dimensions. So far, Islamic law has often been reduced to a normative-legalistic system that is separated from the complex and dynamic realities of life. Through a philosophical approach, this article asserts that Islamic law is not only a set of formal rules derived from revelation, but also a value system that guides humans towards a just, civilized and spiritually meaningful life. The transcendental dimension emphasizes the relationship of law with God as the highest source of authority; the moral dimension highlights ethical orientation and moral formation; while the social dimension underlines the relevance of Islamic law in addressing the problems of justice and the benefit of the people. With a qualitative analysis based on literature study and a normative-philosophical approach, this article concludes that an integrative reconstruction of Islamic law is needed to be able to answer the challenges of modern times without losing its spiritual spirit and ethical values.